2020
DOI: 10.1186/s12882-020-1713-3
|View full text |Cite|
|
Sign up to set email alerts
|

Serum magnesium, mortality and disease progression in chronic kidney disease

Abstract: Introduction Magnesium disorders are commonly encountered in chronic kidney disease (CKD) and are typically a consequence of decreased kidney function or frequently prescribed medications such as diuretics and proton pump inhibitors. While hypomagnesemia has been linked with increased mortality, the association between elevated magnesium levels and mortality is not clearly defined. Additionally, associations between magnesium disorders, type of death, and CKD progression have not been reported. Therefore, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 24 publications
3
26
1
Order By: Relevance
“…In this study, the prevalence of hypomagnesemia was found to be 18.6% [64]. Although in the literature there is heterogeneity in defining the cut-off point for hypomagnesemia, among the different critical values mentioned-0.8 mmol/L, 0.75 mmol/L, and 0.7 mmol/L [69]-the critical value of 0.7 mmol/L used in our study has been widely reported in several studies [25,64,[70][71][72][73] but not in others. It has been stated that hypomagnesemia ranges from 2.0% to 15% in healthy subjects, and between 14% and 48% in type-2 diabetic subjects [25,64,[74][75][76][77].…”
Section: Discussionmentioning
confidence: 49%
“…In this study, the prevalence of hypomagnesemia was found to be 18.6% [64]. Although in the literature there is heterogeneity in defining the cut-off point for hypomagnesemia, among the different critical values mentioned-0.8 mmol/L, 0.75 mmol/L, and 0.7 mmol/L [69]-the critical value of 0.7 mmol/L used in our study has been widely reported in several studies [25,64,[70][71][72][73] but not in others. It has been stated that hypomagnesemia ranges from 2.0% to 15% in healthy subjects, and between 14% and 48% in type-2 diabetic subjects [25,64,[74][75][76][77].…”
Section: Discussionmentioning
confidence: 49%
“…In most of the studies with multiple magnesium categories, the effect estimates of the categories showed a monotonic association between magnesium and all-cause mortality in favour of higher magnesium. In two studies, the association was U-shaped demonstrating an increased risk for all-cause mortality in the highest category with magnesium above 1.27 mmol/L, compared with magnesium concentration in between 1.15 and 1.27 mmol/L in the first study, and magnesium above 1.1 mmol/L compared with magnesium in between 0.7 and 1.1 mmol/L in the second study [17,35]. This was not confirmed by the three other studies that included magnesium categories substantially above the reference range [21,25,40].…”
Section: All-cause Mortalitymentioning
confidence: 98%
“…A recent study with stage 3 and 4 patients found that the serum Mg was not related to the different stages of the glomerular filtration rate. 27 The kidneys play an important role in magnesium homeostasis. Under physiological conditions, 70% to 80% of plasma magnesium are filtered from glomeruli, and more than 95% of this ion is reabsorbed along the tubular system by various coordinated transport processes, leaving only 3%-5% that will be excreted in urine.…”
Section: Discussionmentioning
confidence: 99%